(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
The increase in production volume leads to environmental pollution with residues and waste, the accumulation of various chemical compounds in large quantities in the soil, and negatively affects the ecological state of the soil cover. Priority tasks for providing the population with environmentally friendly products include soil remediation, as well as increasing the yield and quality of agricultural crops. The research results presented in this article are in accordance with Article 6 of the Law of the Republic of Uzbekistan No. 903, which aims to protect, improve, and restore the fertility of contaminated, disturbed, or otherwise degraded soils. Until now, soils of Uzbekistan have been evaluated only by their properties, without taking pollution processes into account. This article examines the soils of the Tashkent region of the Republic of Uzbekistan based on the results of their soil-ecological assessment. Some soil properties, such as mechanical composition, agrochemical properties, degree of salinity, as well as the amount of metals detected in the soils, were analyzed. The methods used to determine soil properties are described in the following works: E.V. Arinushkina’s "Agrochemical Methods of Soil Research" and "Manual on Chemical Analysis of Soils," N.A. Kachinsky’s "Soil Physics," and L. Tursunov’s "Soil Physics." Based on the results of soil properties and the permissible norms of metal content, the Soil Quality Index (SQI) was calculated and the degree of soil health was determined. Using geoinformation system technologies and based on the SQI indicators of the studied areas, the following were developed: an assessment map of soil condition, an assessment map of soil ecological state, and digital maps with a comprehensive soil-ecological assessment.